Effect of an intraoperative infusion of amino acids on body temperature, serum biochemistry, serum insulin and recovery variables in healthy dogs undergoing ovariohysterectomy. (11th August 2018) - Clark‐Price, Stuart C; Phillips, Heidi; Selmic, Laura Elizabeth; Keating, Stephanie C J; Reagan, Jennifer K
Abstract : Change in body temperature (BT), serum biochemistry and recovery variables were compared after infusion of amino acids (AA) or lactated Ringer's solution (LRS) in dogs undergoing ovariohysterectomy. Dogs received eight parts 10 per cent AA and two parts LRS (AA, n=10) or only LRS (CG, n=10) at 10 ml/kg/hour during 90 minutes of anaesthesia. BT was measured during anaesthesia and 60 minutes of recovery. Extubation time and shivering were noted. Serum samples were obtained before anaesthesia (T0), end of anaesthesia (T90) and 18 hours after (T18h). Friedman, Mann‐Whitney, Kruskal‐Wallis or Fisher's exact tests were used for analysis. A decrease in BT of −2.16 (−1.59 to −3.24)°C for group AA and −2.79 (−1.98 to −4.52)°C for group CG was different (P=0.02). Time to extubation was 5 (3–9) minutes for group AA and 9 (5–15) minutes for group CG and was different (P=0.01). Only 30 per cent of dogs in group AA and 100 per cent of dogs in group CG shivered during recovery (P=0.003). Glucose, insulin and blood urea nitrogen at T90 were higher than T0 and T18h for group AA. Dogs receiving intraoperative infusion of AA had a higher BT, extubated sooner and shivered less than control dogs at recovery from anaesthesia.